Comparison of the Body Mass Index (BMI) and the Perception of Body Image in Adolescents from a Conurbation Municipality of Yucatán - Peña, Dra.Yolanda Oliva (Advances in Social Sciences Research Journal, 2022)
- Adolescence is a time of important changes at all levels, and a vital stage for health prevention. The objective of the work is to analyze the concordance between the BMI and the perception of body image in students of a suburban community. Materials and methods. Quantitative, observational, cross-sectional study carried out on 120 students, 52.5% men and 47.5% women, aged between 12 and 16 years, from a suburban town in the City of Mérida. Self-administered questionnaire with the Stunkard pictogram, to record the perception of body image. To calculate the body mass index (BMI), anthropometric measurements of weight and height were recorded, updated at the school. Results. The findings, regarding the perception of body image, showed a non-significant discrepancy (k= -.007, p= .876); in women it was insignificant and not significant (k= .051, p= .434); As for men, non-significant discrepancy was observed (k= -.056, p= .332). Conclusions. When performing the Kappa analysis in a general way, no significant agreement was found in the sample. When analyzing by sex, only insignificant (poor) concordance and no statistical significance were found in women.Palabras clave: Índice de masa corporal, Imagen corporal, Adolescencia, Yucatán.